La santé et la sécurité des élèves en centre de formation professionnelle : approche, représentations, et genre - Céline Chatigny; Jessica Riel (Perspectives Interdisciplinaires sur le Travail et la Santé)
The purpose of this research was to explore occupational health and safety (OHS) issues in vocational training centres, including the OHS of students. Several methods were used with the 76 participants (managers, professionals, teachers, students): individual and group interviews, self-administered questionnaires, observations, and the analysis of documents dedicated to OHS teaching. These methods made it possible to study OHS experiences, recommendations, and approaches, as well as the roles and factors that influence representations and learning. Most of the students were from the fields of hairdressing (20) and automated electro-mechanic systems (19). The results revealed that the representations differed according to the group, that the students’ had OHS concerns, particularly about impairment to their health, which were greater than what their counsellors believed they were, that these were higher among hairdressing students, and that there were gendered approaches to OHS. Further research avenues and aspects to be developed are then discussed.